Wave fields in the stratified fluid-saturated porous half-space induced by dislocation sources - Song, Y.; Shi, J. (Archives of Mechanics, 2017)
In this study, the wave fields induced by both tensile and shear displacement dislocations in stratified fluid-saturated porous media are computed by using the reflection and transmission matrix method. The components of the source discontinuity vector across the source plane to describe those tensile and shear faults are explicitly displayed by using the surface vector harmonics. Numerical examples for a two layer model subjected to tensile and shear dislocations are provided. From the waveforms of surface displacements, the arrivals of transmitted and converted PS and SP waves at the interface of the two layer model can be clearly observed.